A double-blind, randomised, crossover trial of two botulinum toxin type A in patients with spasticity - Guarany, Fábio Coelho (2013)
Background: Botulinum toxin type A (btxA) is one of the main treatment choices for patients with spasticity. ProsigneH a new released botulinum toxin serotype A may have the same effectiveness as BotoxH in focal dystonia. However, there are no randomized clinical trials comparing these formulations in spasticity treatment. The aim of our study was to compare the efficacy and safety of ProsigneH with BotoxH in the treatment of spasticity. Methodology/Principal Findings: We performed a double-blind, randomized, crossover study consisting of 57 patients with clinically meaningful spasticity. The patients were assessed at baseline, 4 and 12 weeks after ProsigneH or BotoxH administration. The main outcomes were changes in the patients’ Modified Ashworth Scale (MAS), Functional Independence Measure (FIM) and Pediatric Evaluation of Disability Inventory (PEDI) scores and adverse effects related to the botulinum toxin. Both of the toxins were significantly effective in relieving the level of spasticity in adults and children. There were no significant differences found between the ProsigneH and BotoxH treatments regarding their MAS, FIM and PEDI scores. Likewise, the incidence of adverse effects was similar between the two groups. Conclusion: Our results suggest that ProsigneH and BotoxH are both efficient and comparable with respect to their efficacy and safety for the three month treatment of spasticity.